The response of tomato, paprika, sunflower, and soybean to low rates of nicosulfruon - Brankov, Milan; Dragičević, Vesna; Tabaković, Marijenka; Simić, Milena (Acta herbologica, 2022)
Drift is the movement of plant protection product droplets through the air and can affect any non-target organism or the environment. In fact, there are three possible scenarios that can be considered as drift: particle drift, volatility, and contamination of the spray tank. Significant damages that can occur as a consequence of drift are damages to neighbouring crops, environmental pollution, lower level of efficiency of the applied herbicide, while in the case of tank contamination, injuries can occur only in the treated field. In order to examine the negative consequences of nicosulfuron drift, four crops were grown in a greenhouse and treated with low doses of herbicide, after which they were returned to cultivation and after 21 days the effects of applied treatments were assessed through visual assessment of injury, dry weight, leaf height, and leaf area. Soybean was the most tolerant to nicosulfuron, while paprika was the most sensitive. Based on the obtained results, it can be concluded that low doses of nicosulfuron expressed different effects on the tested plants and that it is necessary to take precautionary measures to prevent herbicides from spreading to neighbouring plants.